Relasi Ontologis Qudrah Allah dan Eksistensi Hukum Islam - Matondang, Maulidya Mora; Faisar Ananda; Nurasiah (Kartika: Jurnal Studi Keislaman, 2025)
Philosophical studies of Islamic law within the literature of uṣūl al-fiqh have predominantly focused on ethical debates concerning good (ḥusn) and evil (qabḥ), while giving relatively little attention to the issue of power (qudrah). This imbalance risks causing a conceptual disorientation in understanding the ontological foundations of legal authority in modern Islamic law. This article argues that divine power (qudrah) possesses a fundamental ontological relation to the very existence of Islamic law. Employing a qualitative library-based methodology, the study integrates the Sunni theological theory of qudrah with the theory of taklīf in uṣūl al-fiqh. The analysis demonstrates that qudrah understood as God’s capacity to bring things into existence or to annihilate them in accordance with His will (irādah) constitutes the foundational condition that enables taklīf, defined as the imposition of legal and moral obligations derived from God’s attribute of speech (kalām), to operate meaningfully. Although the relationship between qudrah and law is not direct, God’s absolute power serves as a prerequisite for the existence of legal subjects (mukallaf), their capacity to perform the Sharīʿah, and the enforcement of legal consequences in both worldly and eschatological realms. Consequently, qudrah functions as an ontological foundation affirming divine sovereignty behind all manifestations of Islamic law